Do the risk factors for developmental dysplasia of the hip differ according to gender? A look from another perspective - (:unkn) unknown (WILEY, 2019)
Aim The aim of the present study was to examine if there were gender differences in risk factors in 4415 infants who were evaluated through a physical examination and hip ultrasonography (USG). Methods Physical examination of the hip and hip USG were performed on 4415 infants by the same paediatric orthopaedics specialist. Barlow and Ortolani tests were performed together with the evaluation for the limitation of abduction. Ultrasonographic hip examination was performed according to the Graf technique. The birth records of all the infants were examined, and anamneses (genetic disease, maternal age, delivery type, swaddling, multiple pregnancies, duration of gestation period, gravida, birthweight, breech presentation, oligohydramnios and family history) were obtained from the families. Any accompanying musculoskeletal (torticollis, pes equinovarus, congenital knee dislocation) abnormality was recorded. Results Pathological hip was determined in 149 (3.37%) of 4415 infants. In males, gestational week, family history, breech presentation, swaddling, congenital knee dislocation and limited abduction were observed to be significant for the presence of developmental dysplasia of the hip (DDH). In females, significant factors for the presence of DDH were determined to include birthweight, gestational week, breech presentation, multiple pregnancy, accompanying oligohydramnios, torticollis, pes equinovarus and limited abduction. Conclusion Risk factors for DDH can differ according to gender.
Keywords: developmental dysplasia of the hip; gender difference; risk factors; ultrasonography; CLINICAL SIGN; DIAGNOSIS; ABDUCTION; DISLOCATION; LIMITATION; PREVALENCE; UNIVERSAL; AUSTRALIA; CLUBFOOT; NEWBORN